Ultrafast and Stable Li‐(De)intercalation in a Large Single Crystal H‐Nb2O5 Anode via Optimizing the Homogeneity of Electron and Ion Transport. Issue 22 (20th April 2020) - Song, Zihan; Li, Hui; Liu, Wei; Zhang, Hongzhang; Yan, Jingwang; Tang, Yongfu; Huang, Jianyu; Zhang, Huamin; Li, Xianfeng
Abstract: Exploring anode materials with fast, safe, and stable Li‐(de)intercalation is of great significance for developing next‐generation lithium‐ion batteries. Monoclinic H‐type niobium pentoxide possesses outstanding intrinsic fast Li‐(de)intercalation kinetics, high specific capacity, and safety; however, its practical rate capability and cycling stability are still limited, ascribed to the asynchronism of phase change throughout the crystals. Herein this problem is addressed by homogenizing the electron and Li‐ion conductivity surrounding the crystals. An amorphous N‐doped carbon layer is introduced on the micrometer single‐crystal H‐Nb2 O5 particle to optimize the homogeneity of electron and Li‐ion transport. As a result, the as‐prepared H‐Nb2 O5 exhibits high reversible capacity (>250 mAh g −1 at 50 mA g −1 ), unprecedented high‐rate performance (≈120 mAh g −1 at 16.0 A g −1 ) and excellent cycling stability (≈170 mAh g −1 at 2.0 A g −1 after 1000 cycles), which is by far the highest performance among the H‐Nb2 O5 materials. The inherent principle is further confirmed via operando transmission electron microscopy and X‐ray diffraction. A novel insight into the further development of electrode materials forlithium‐ion batteries is thus provided. Abstract : Micrometer‐sized single crystal H‐Nb2 O5 with an amorphous N‐doped carbon shell (N‐C@MSC‐Nb2 O5 ) is designed to optimize the homogeneity of electron and ion transport, which dramatically improves its electrochemical reaction kinetics and synchronism of phase change during (de)intercalation. Therefore, N‐C@MSC‐Nb2 O5 shows a better high‐rate performance than most Li4 Ti5 O12 ‐based and T‐Nb2 O5 ‐based anode materials for lithium‐ion batteries.